Reply: COVID-19 drug research and the cohort multiple randomised controlled trial design. Issue 3 (15th September 2022) - Porcher, Raphaël; Ravaud, Philippe; Resche-Rigon, Matthieu; Tharaux, Pierre-Louis; Mariette, Xavier; Hermine, Olivier
We read with interest the comment of R. Dal-Ré on the CORIMUNO-19 trials design [1–5]. The key argument is that the cohort multiple randomised controlled trial (cmRCT) design implies an alteration of the informed process that can only be justified if three requirements are fulfilled: the research has important social value, it poses no more than minimal risks to participants, and it would be impracticable to carry out without consent process modification [6]. R. Dal-Ré acknowledges that the first two requirements were fulfilled for CORIMUNO-19 trials, but argues that, given the huge number of patients hospitalised with severe or critical coronavirus disease 2019 (COVID-19) in March 2020, trials would have been feasible without consent modification. The use of cohort multiple randomised controlled trials and epidemic crises https://bit.ly/39Obd4N